Dynamics and viscosity of ‘a’a and pahoehoe lava flows of the 2012–2013 eruption of Tolbachik volcano, Kamchatka (Russia) - Belousov Alexander; Belousova Marina (My University, 2018)
The 2012–2013 flank eruption of Tolbachik volcano (Kamchatka) lasted 9 months and produced 0.54 km3 of basaltic trachyandesite lava, thus becoming one of the most voluminous historical lava effusions of basic composition in subduction-related environments globally. From March to July 2013, the volcano monotonously erupted lava of constant composition (SiO2 = 52 wt%) with a nearly stable effusion rate of 18 m3/s. Despite the uniform eruptive and emplacement conditions, the dominant style of lava propagation throughout that time gradually changed from ‘a’a to pahoehoe. We report results of instrumental field measurements of the ‘a’a and pahoehoe flow dynamics (documented with time-lapse cameras) as well as the lava viscosity determined by flow rate and shear stress (using penetrometer) methods. Maximal propagation velocities of the ‘a’a fronts ranged from 2 to 25 mm/s, and those of the pahoehoe from 0.5 to 6 mm/s. The flow front velocities of both lava types experienced short-period fluctuations that were caused by complex flow mechanics of the advancing flow lobes. Minimal viscosities of lava of the ‘a’a lobes ranged from 1.3 × 105 to 3.3 × 107 Pa s (flow rate method), and those of the pahoehoe from to 5 × 103 to 5 × 104 Pa s (shear stress method). Our data include the first ever measured profiles of viscosity through the entire thickness of actively advancing pahoehoe lava lobes. We have found that both the ‘a’a and pahoehoe flows were fed by identical parental lava, which then developed contrasting rheological properties, owing to differences in the process of lava transport over the ground surface. The observed transition from the dominant ‘a’a to the dominant pahoehoe propagation styles occurred due to gradual elongation and branching of the lava tube system throughout the course of the eruption. Such evolution became possible because the growing lava field, composed of semisolidified flows, provided an environment for shallow subsurface intrusions and internal migrations of lava that, with time, developed into branches of the lava tube system. Based on our data, we propose phenomenological models of the ‘a’a and pahoehoe flow mechanics.
Keywords: Tolbachik volcano; Lava flow velocity; Viscosity of lava; ‘A’a; Pahoehoe